THE VENDIAN SYSTEM OF SIBERIA AND A STANDARD STRATIGRAPHIC SCALE - Khomentovsky V.V. (My University, 1986)
In Siberia Vendian is equated with a Yudoma Complex or Yudomian. Yudomian deposits of the Siberian Platform and adjacent geosynclines differ greatly in facies and thickness. According to the composition and structure of Yudomian deposits, four facies provinces may be recognized on the platform. Local stratigraphic charts for each province are presented and their correlation and possibility to subdivide the Vendian System in Siberia into three horizons or stages are substantiated. The upper stage (Nemakit–Daldyn), on the basis of palaeontological evidence, is in its turn subdivided into two zones: Anabarites trisulcatus and Purella antiqua.The most important Early Baikalian rearrangement is proved to take place around 800±50 Ma. The pre-Vendian (Late Baikalian) movements, though less intensive, make the determination of the Yudomian lower boundary easier.The specific character of Vendian biostratigraphy is discussed involving all groups of the organic remains, that causes the necessity of recognition, subdivision and correlation on the basis of the whole complex of data.The boundary between the Vendian System and the Lower Cambrian Tommotian Stage (in type section) is proved to conform to the base of the Pestrozvet Formation, which divides the A. sunnaginicus and P. antiqua zones.
Keywords: Vendian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский